Evaluasi dan Perancangan Prototype Perbaikan Antarmuka Sistem Informasi Administrasi Terpadu (SIAT) Fakultas Pertanian Universitas Brawijaya Malang dengan menggunakan metode WEBUSE dan Human Centered Design (HCD) - Yeni Amelia Br Tarigan; Satrio Hadi Wijoyo; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Faculty of Agriculture, Brawijaya University, Malang has a web application called the Integrated Administrative Information System (SIAT). The web application has several problems such as improper table arrangement, unequal size of content, and sloppy writing. This study aims to evaluate the appearance of the current web application and design prototype improvements which will then be evaluated in order to reduce the problems contained in the SIAT web application and produce improvement solutions so as to make SIAT even better. To determine the usability value, an evaluation is carried out using the Web Usability Evaluation (WEBUSE) which consists of four categories, namely Content, Organization and Readability, Navigation and Links, User Interface Design and Performance and Effectiveness. Improvement prototype design solution is made using the Human Centered Design (HCD) method which has several stages, namely understanding and determining the user context, specification of user needs, designing solutions and evaluating solution designs. The results of this study indicate that the design of the improved prototype made is better than the current web application design so that the usability value in each WEBUSE category has increased. Previously, there were several points in the WEBUSE category that resulted in poor and moderate usability levels, but after improvements were made, all points per WEBUSE category were at the good usability level .The design of this prototype produces a design solution that has a higher level of user satisfaction.